Lifestyle changes and outcomes of older adults with mild cognitive impairment: A 4-year longitudinal study. (May 2021) - Katayama, Osamu; Lee, Sangyoon; Bae, Seongryu; Makino, Keitaro; Shinkai, Yohei; Chiba, Ippei; Harada, Kenji; Shimada, Hiroyuki
Highlights: Mild cognitive impairment (MCI) can revert to normal cognition (NC). No reports exist on lifestyle activity change patterns in older adults with MCI. We determined the lifestyle activity change patterns among older adults with MCI. Multidomain lifestyle activities, more likely led to reversion of MCI to NC. Abstract 1 : Background: Longitudinal studies have shown that mild cognitive impairment (MCI) reverts to normal cognition (NC). However, we could not find any reports on the examination of changes in lifestyle activity patterns in older adults diagnosed with MCI and their outcomes, in a longitudinal study. We determined the changes in lifestyle activity patterns among older adults with MCI. Methods: The participants in this study were 769 community-dwelling older adults aged ≥65 years with MCI at baseline. Four years later, participants were categorized into reverters, maintainers, and converters who reverted from MCI to NC, maintained MCI, and had global cognitive impairment or Alzheimer disease, respectively. We used latent class analysis to classify changes in instrumental activities of daily living, and in cognitive, social, and productive activities of the participants. Subsequently, a multinomial logistic regression analysis was performed with reversion status and class membership as the dependent and independent variables, respectively. Results: The reversion rate of 769 participants was 33.3%. The reverters maintained multidomain lifestyle activities, converters discontinued multidomain lifestyle activities or were inactive, and maintainers maintained productive activities. According to the logistic regression analysis, the activity patterns of those who continued to engage in multidomain lifestyle activities and start activities, were more likely to help in reverting from MCI to NC ( P < 0.05). Conclusions: Community-dwelling older adults with MCI who continued their multidomain lifestyle activities were more likely to revert to NC. Even if it does not revert to NC, continuing productive activities is important to maintaining MCI without converting.